Cellular concrete with preformed foam and lightweight aggregates (Nexo Revista Científica, 2023)
The aim of this work is developed cellular concrete mixtures using preformed foam and lightweight aggregates, for the production of concrete blocks in accordance with the indicated in the Nicaraguan Mandatory Technical Standard. Six concrete mixtures containing lightweight aggregates like lime, pumice and polyethylene fiber were made; furthermore, foam made out of a pressurized dissolution of Texapon N70 in water. Cubes and cylindric specimens were cast and moist-cured for 7 days, and tested to know their compressive strength at 28 days. The results show that the nature of the aggregates, as well as the foam content in the mixtures influenced their densities. It was observed that the percentage of cementing material used is directly proportional to its final strength. The results obtained for compressive strength were comparable to the minimum requirements indicated in the standard for structural blocks, in addition to serving as thermal and acoustic insulation thanks to its high percentage of voids.